The behavior in seeking information UNAM researchers belonging to the National System of Researchers - Castillo Barrera, Silvia (Revista General de Información y Documentación, 2017)
This paper addresses the behaviors of UNAM researchers belonging to the National System of Researchers (SNI) area IV of Humanities and behavior to make your search for information to develop their research. The research was to find out how to perform the search for information; What are the sources and information resources they use; what language and seniority dating consulting information sources; whether to delegate the search for information to another person or intermediary; and if there is any influence or relationship in their information behavior among factors such as age, employment status and years of service as researchers in the SNI, with the use of libraries and the Internet, and monographs and periodicals. Technical survey using the questionnaire, which was applied to a stratified sample for greater representativeness of the study was applied. The analysis of the results was descriptively and by using statistical calculations to see if there was any relationship between the elements described above.
Keywords: Information behavior; information search; Information resources; Information sources; SNI researchers.